Averaging of randomly perturbed evolutionary equations - Kolomiets, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Evolutionary equations with coefficients perturbed by diffusion processes are considered. It is proved that the solutions of these equations converge weakly in distribution, as a small parameter tends to zero, to a unique solution of a martingale problem that corresponds to an evolutionary stochastic equation in the case where the powers of a small parameter are inconsistent.